Pengaruh Krisis Ekonomi Terhadap Fungsi Konsumsi Rumah Tangga di Indonesia Penerapan: Absolute Income Hypothesis - Saraswati, Birgitta Dian; Khusaini, M. (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No.1, Februari 2018 (pp. 1-144)DO - 10.24843/JEKT.2018.v11.i01.p11, 2018)
This study aimed to identify how household consumption is influenced by economic crises in 1997 according to Keynes absolute income hypothesis. Using Chow Test and Partial Adjustment Models, the result show that the economic crisis in 1997 resulted in a structural change in household consumption in Indonesia clearly visible from MPC value before the economic crisis is bigger than the MPC after the crisis. The economic crisis has an effect on household consumption in Indonesia in both the short term and in the long term.
Keywords: Konsumsi Rumah Tangga, Hipotesis Pendapatan Absolut, Pendapatan, Krisis Ekonomi, Marginal Propensity to Consume